Interviewing Neuroscientists for an Undergraduate Honors Project - Montiel, Catalina (J Undergrad Neurosci Educ, 2017)
Honors projects that supplement standard coursework are a widely used practice in undergraduate curricula. These projects can take many forms, ranging from laboratory research projects to performing service learning to literature analyses. Here we discuss an honors project focused on interviewing neuroscientists to learn about individual scientific practice and career paths, and synthesizing the resulting information into a personal reflection essay. We detail step-by-step instructions for performing this type of project, including how to develop interview questions, a sample project timeline, deliverables, learning objectives and outcomes, and address potential pitfalls. We provide sample interview questions, an interview solicitation email, and in the supplemental materials an example student reflection essay, assessment rubrics, and the transcription of a student-conducted interview of Drs. John Godwin and Santosh Mishra of North Carolina State University. This type of project is a promising method to enable student-researcher communication, and potentially useful to a broad spectrum of both honors and non-honors neuroscience coursework.